Correction: Effects of UV-B radiation on the infectivity of Magnaporthe oryzae and rice disease-resistant physiology in Yuanyang terraces. Issue 3 (20th February 2018) - Li, Xiang; He, Yongmei; Xie, Chunmei; Zu, Yanqun; Zhan, Fangdong; Mei, Xinyue; Xia, Yang; Li, Yuan
Abstract : Correction for 'Effects of UV-B radiation on the infectivity of Magnaporthe oryzae and rice disease-resistant physiology in Yuanyang terraces' by Xiang Li et al., Photochem. Photobiol. Sci., 2018, 17, 8–17.